Hubungan Pengetahuan Gizi dan Kebiasaan Makan Remaja dengan Status Gizi pada Mahasiswa Kebidanan Universitas Harkat Negeri - Meyliya Qudriani; Nora Rahmanindar; Ilma Ratih Zukrufiana; Evi Zulfiana (Lembaga Pengembangan Kinerja Dosen, 2026)
Nutritional problems in adolescents are complex, as evidenced by the high rate of iron deficiency anemia, especially among girls (23%), as well as malnutrition and overnutrition. According to SKI (2023), nutritional problems in adolescents include thinness and extreme thinness reaching 7.6%, while adolescents who are overweight reach 12.1%, and those who are obese reach 4.1%. The objectives are to determine the knowledge of balanced nutrition and eating habits of students in their daily lives and to identify the relationship between knowledge and eating habits with nutritional status. This study used a cross-sectional design with a population of 45 students from the Midwifery Study Program at Harkat Negeri University. The sampling technique used was total sampling. The research instrument was a questionnaire distributed via Google Form, while nutritional status was obtained by measuring BMI. Univariate and bivariate analyses were used. The majority of respondents were aged 20 years (44.5%), had good nutritional knowledge (59.1%), poor eating habits (63.6%), and normal nutritional status (68.2%). In the bivariate analysis, there was no significant relationship between nutritional knowledge and eating habits with the nutritional status of students (p-value >0.05). Conclusion The majority of students had good understanding of nutrition, but not of eating habits. It is hoped that students can maintain eating habits with balanced nutrition in order to achieve normal nutritional status. Keywords: Nutrition Knowledge; Eating Habits; Nutritional Status